Effect of Yak Meat to the Daily Ration of Scalded Rats for Wound Healing - Wang HJ; Feng YP; Tian XX; Wu XH; Hao LZ; Li Y; Mei SJ (Dove Medical Press, 2023)
Hong-Jin Wang,1,* Yan-Ping Feng,1,* Xiao-Xia Tian,2 Xiao-Han Wu,1 Li-Zhuang Hao,2 Yi Li,1 Shi-Juan Mei3 1Department of Burns and Plastic Surgery, Affiliated Hospital of Qinghai University, Xining, Qinghai, 810012, People's Republic of China; 2Qinghai University, Academy of Animal Science and Veterinary Medicine, Key Laboratory of Plateau Grazing Animal Nutrition and Feed Science of Qinghai Province, Xining, Qinghai, 810016, People's Republic of China; 3Department of Oncology, affiliated Hospital of Qinghai University, Xining, Qinghai, 810010, People's Republic of China*These authors contributed equally to this workCorrespondence: Yi Li, Department of Burns and Plastic Surgery, Affiliated Hospital of Qinghai University, No. 29 Tongren Road, Xining, Qinghai province, 810010, People's Republic of China, Tel +86-13709760887, Email liyily5t@126.com Shi-Juan Mei, Department of Oncology, Affiliated Hospital of Qinghai University, No. 29 Tongren Road, Xining, Qinghai province, 810010, People's Republic of China, Tel +86-15009715352, Email meishijuanmsj8g@126.comObjective: Treatment of burn wound healing involves infection, nutrition, psychology and rehabilitation, and proper nutritional support can promote wound healing, enhance immune function and reduce the incidence of complications. This study aimed to investigate the effects of feed containing yak meat on scalded rats' body condition and wound healing.Methods: Adopting a two-factor factorial design, the growth performance, food intake, body weight, and Lee's index of rats were measured. The wound conditions of scalded rats with different feeds (basic, basic + yak meat, and basic + yellow beef) were observed at different periods, and their wounds' hematoxylin and eosin (H&E) staining states were detected. The proliferating cell nuclear antigen (PCNA)-positive cells and apoptosis were analyzed to evaluate the effects of feed on the wound healing of scalded rats.Results: The feed intake was the highest in the yellow beef feed group and the lowest in the yak meat feed group. The body weight was the highest in the yak meat feed group and the lowest in the yellow beef feed group. Furthermore, 45 days after scalding, the obesity index in the yak beef feed group was the closest to that of the rats before scalding. The wound recovery of the rats in the yak meat feed group was the best at 30 days, and the H&E staining results also proved that the recovery effect of the scalded rats in the yak meat feed group was better than other two groups. According to the results of PCNA and apoptosis, the yak meat feed group had lower positive cell rate and faster wound healing.Conclusion: The rats in the yak meat feed group recovered better than those in the other groups, and the yak beef feed had the best effect on the wound healing of the scalded rats.Keywords: scalded rats, yak meat feed, yellow beef feed, basic feed, wound healing